Effect of arc corrugation initiation on the thermo-hydraulic performance and entropy generation of the corrugated tube. (November 2022) - Kumar, Krishan; Kumar, Rajan; Bharj, Rabinder Singh; Said, Zafar
Abstract: It's important to know which corrugation start provides the best heat transfer performance with the least frictional losses. Thus, the present work focuses on the performance of corrugated tubes with different corrugation initiation. The different types of arc corrugations (outward arc, inward arc, outward arc-inward arc, and inward arc-outward arc) are used for assessing the entropy generation and thermo-hydraulic performance of the tubes under the application of constant wall heat flux. The different corrugation starts have a different effect on the thermo-hydraulic and entropy generation performance. For all the considered flow rates, the outward arc-inward arc configuration has the highest Nusselt number. The combination of inward and outward arc corrugations results in better heat transfer, but this improved heat transfer is at the expense of the pressure drop. The total and heat transfer entropy generation in the corrugated and smooth tubes reduce with an increment in the Reynolds number, while frictional entropy generation enhances. The outward arc-inward arc configuration results in the lowest total entropy generation at the highest Reynolds number and it is 0.398 W/K. All the corrugated tubes have entropy generation number less than unity, which is advantageous because of better heat transfer and lesser system irreversibility. Highlights: Effect of corrugation initiation on the thermo-hydraulic performance in the arc corrugated channels is assessed. Inward arc, outward arc, inward arc-outward arc, and outward arc-inward arc are the four corrugation configurations used. Augmentation entropy generation number is achieved below unity under the considered conditions. All of the corrugation configurations have been found to be suitable for applications requiring improved heat transfer.